Effects of the Information Motivation and Decision-making Skills Program on Preventive Behaviors towards Repeated Pregnancy among Adolescent Mothers - Mala, Athitaya; Lapvongwatana, Punyarat; Chansatitporn, Nutkamol; Sirimai, Korakot (Nursing Science Journal of Thailand, 2022)
Purpose: To examine the effects of the Information, Motivation and Decision-making Skills Program on preventive behaviors towards repeated pregnancy among adolescent mothers. Design: Two-group pretest-posttest quasi-experimental design. Methods: Participants were adolescent mothers younger than 20 years of age who attended the delivery care unit at a university hospital. Two comparable adolescent mothers were selected to participate in the study, 27 subjects served as an intervention group, 25 of them served as a comparison group. The comparison group received usual care. The intervention group received the program consisted of 3 steps: 1) providing information on repeated pregnancy prevention and contraception, 2) building motivation and positive attitude towards repeated pregnancy prevention, and 3) building skills for repeated pregnancy prevention. Data were collected three times: before the experiment, immediately after, and 6-8 weeks follow-up. Self-administered questionnaires, including knowledge, attitudes, decision making, and preventive behaviors towards repeated pregnancy were used. Data were analyzed using descriptive statistics, independent t-test, and repeated measures ANOVA. Main findings: The mean score of knowledge (F = 28.34, p < .001) and attitude (F = 6.19, p = .005), in the intervention group were significantly higher than the comparison group from baseline to immediately after intervention and 8-week follow-up. The mean score of decision-making skills in the intervention group became increasing but did not significantly differ from the comparison group (F = 1.74, p = .193), and the mean score of repeated pregnancy preventive behaviors became higher at 8-week follow-up but did not significantly differ from the comparison group (F = 3.07, p = .08). Conclusion and recommendations: This program which brought the spouses to help motivate the adolescent mothers could assist the mothers to perform preventive behaviors towards repeated pregnancy. Therefore, nurses should apply this program to promote preventive behaviors among adolescent mothers towards repeated pregnancy.